Gambaran Penggunaan Model Role Playing Pada Kegiatan Ekstrakurikuler Palang Merah Remaja di SMP Negeri 18 Padang - Adrizon Rizki; Ismaniar Ismaniar; Jalius Jalius (Universitas Negeri Padang, 2018)
This research was motivated by the implementation of extracurricular activities in the Palang Merah Remaja at SMPN 18 Padang, this was marked by the high attendance, enthusiasm of learning, and the activeness of the students in the activity. Allegedly one of the factors was caused by the role playing learning model applied by the coach's brother. The purpose of this study is to describe the use of role playing models which are seen from the readiness of students, role selection, role play, and evaluation of the activities of the Palangf Mewrah Remaja in SMPN 18 Padang. This type of research is quantitative descriptive research. The population and sample in this study were students who participated in extracurricular youth red cross. Data collection techniques using questionnaires, with data collection tools questionnaire (questionnaire) and data analysis techniques used percentage formula. The results of the study found that the readiness of students, role selection, role play, and evaluation of extracurricular activities in the youth red cross were categorized as good. So it can be concluded that the use of role playing models proved to lead to the successful implementation of extracurricular activities in the Palang Merah Remaja. Based on the results and conclusions of the researchers it is suggested that in the implementation of PMR activities, the coaches will continue to use this role playing model by continuing to make various modifications so that it will run well.